A randomised, controlled study on the effects of a short-term endurance training programme in patients with major depression. Issue 1 (24th October 2006) - Knubben, K; Reischies, F M; Adli, M; Schlattmann, P; Bauer, M; Dimeo, F
Abstract : Objective: To evaluate the short-term effects of exercise in patients with major depression. Design: Prospective, randomised, controlled study. Setting: A university hospital. Patients: A consecutive series of 38 inpatients with a major depression episode undergoing standard clinical antidepressant drug treatment. Interventions: Patients were randomly assigned to an exercise (walking, n = 20) or placebo (low-intensity stretching and relaxation exercises, n = 18) group. Training was carried out for 10 days. Main outcome measurements: Severity of depression assessed with the Bech-Rafaelsen Melancholy Scale (BRMS) and the Center for Epidemiologic Studies Depression scale (CES-D). Results: After 10 days, reduction of depression scores in the exercise group was significantly larger than in the placebo group (BRMS: 36% v 18%; CES-D: 41% v 21%; p for both = 0.01); the proportion of patients with a clinical response (reduction in the BRMS scores by more than six points) was also larger for the exercise group (65% v 22%, p<0.01). Conclusions: Endurance exercise may help to achieve substantial improvement in the mood of selected patients with major depression in a short time.